If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 7x + -69 = 0 Reorder the terms: -69 + 7x + 5y = 0 Solving -69 + 7x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '69' to each side of the equation. -69 + 7x + 69 + 5y = 0 + 69 Reorder the terms: -69 + 69 + 7x + 5y = 0 + 69 Combine like terms: -69 + 69 = 0 0 + 7x + 5y = 0 + 69 7x + 5y = 0 + 69 Combine like terms: 0 + 69 = 69 7x + 5y = 69 Add '-5y' to each side of the equation. 7x + 5y + -5y = 69 + -5y Combine like terms: 5y + -5y = 0 7x + 0 = 69 + -5y 7x = 69 + -5y Divide each side by '7'. x = 9.857142857 + -0.7142857143y Simplifying x = 9.857142857 + -0.7142857143y
| 84/3x+9+7=9 | | 36/3x+7=10 | | 7x+91/3+51=93 | | 14x-2/2+7=27 | | 7x/3+81=117 | | 3(1+x)=2(x-2) | | 96=454+24h | | m-2=n | | x-10/5-8=5 | | 4x/2+7=21 | | 2m-4=4n | | 0.4a=9.2 | | 80a+a^2=18a | | ((12a^-3b^4c^2)/(-4a^-7b^-2c))^-2 | | 27=(x^2-.4x) | | 3(6x-7)(3x+7)=0 | | 324=h(h+12)(h+3) | | 10x+30=20+11x | | 3(1x)=2(-2) | | 15y=3y+48 | | 9x^2+24xy+16y^2+90x-130y=0 | | B-9/12=-3 | | 1140=8x+11x | | 5(x-6)+3=33 | | 2x^2-4x=-18 | | 2p/3-5=7 | | -5y-3=4y+13 | | 6/5(8x+2)=-36 | | 8x-.5=3 | | 0=x^2-9x+25 | | 4(x+10)=60 | | 1.5=7.5 |